1997
DOI: 10.1007/s002340050365
|View full text |Cite
|
Sign up to set email alerts
|

Gelastic seizures in a child with focal cortical dysplasia of the cingulate gyrus

Abstract: We present a case of gelastic seizures in a child with focal cortical dysplasia of the anterior cingulate gyrus. This is only the second published case of a confirmed lesion at this site presenting in such a way. The underlying neurological mechanism is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 2 publications
1
29
1
1
Order By: Relevance
“…Various aetiologies in the region of prefrontal, temporal cortex, internal capsule, hypothalamus, thalamus, lesions in and around brainstem and the cerebellar pathways have been known to be associated with pathological laughter [2,3,5,6]. Gelastic seizures seen in hypothalamic hamartomas sometimes mimics pathological laughter [7].…”
Section: Introductionmentioning
confidence: 99%
“…Various aetiologies in the region of prefrontal, temporal cortex, internal capsule, hypothalamus, thalamus, lesions in and around brainstem and the cerebellar pathways have been known to be associated with pathological laughter [2,3,5,6]. Gelastic seizures seen in hypothalamic hamartomas sometimes mimics pathological laughter [7].…”
Section: Introductionmentioning
confidence: 99%
“…The commonest association is with hypothalamic hamartoma (HH), a nonneoplastic malformation rising between the mammillary body and the tuber cinereum [1, 2]. Other sites in the brain that are associated with GS are the frontal [3, 4, 5, 6, 7, 8, 9]and temporal regions [10]. Children with HH and GS usually present with seizures early in life, often prior to 1 year of age [2, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…ACC is considered part of the emotional smile pathway (Lauterbach et al, 2013;Morecraft, Stilwell Morecraft, & Rossing, 2004), and several authors have reported the association of ACC function with smile and laughter and it is known that ACC lesions can be associated with gelastic seizure (Alkawadri, Mickey, Madden, & Van Ness, 2011;Alkawadri, So, Van Ness, & Alexopoulos, 2013;Arroyo et al, 1993;McConachie & King, 1997). Intraoperative stimulation of the ACC has been reported to induce laughter (Iwasa et al, 2002;Sperli, Spinelli, Pollo, & Seeck, 2006).…”
Section: Discussionmentioning
confidence: 97%